PENGARUH PERSEPSI KEBERMANFAATAN, KEMUDAHAN, DAN RISIKO TERHADAP MINAT PENGGUNAAN LAYANAN PEMBAYARAN DIGITRAL PADA MAHASISWA AKUNTANSI - Nesha Nenandha (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2022)
People in Indonesia are starting to get used to using a digital payment system that can be done anywhere and anytime during transaction activities. Therefore, the researcher conducted a study entitled: